Facial asymmetry due to condylar hyperplasia - Gopal Sharma; Deepa Das; Avinash Kumar Singh; Chandan Dolare (Wolters Kluwer Medknow Publications, 2012)
Facial asymmetry can be attributed to various conditions from developmental to malignancy. Depending upon the etiology, the treatment plan has to be modified- With the latest imaging modalities we are in a better position to find whether the asymmetry is due to soft tissue or bone pathology. The case of a patient who reported with facial asymmetry and whose radiograph showed unilateral condylar hyperplasia is presented here.